Wayang as Da’wah Medium of Islam according to Sunan Kalijaga - Hifni Nasif; May Putri Wilujeng (Universitas Darussalam Gontor, 2018)
Wayang is tradition contains phylosophical values and great teachings. For Javanese people, wayang is not only as performance, but therein the life guidance. At the beginning, wayang was used as a media for worshipping to ‘Hyang’ (God) about 1500 BC. It was also used as medium for spreading the doctrine of Islamic teachings. Because of the closeness of wayang performance in the people’s heart, Walisanga made wayang as one of their da’wah medium. Among the famous preacher (da’i) that uses wayang was Sunan Kalijaga. In order to researcher used al-Nahl 16:125 as a cornerstone in looking at the method of da’wah according to Sunan Kalijaga, namely methods of da’wah bi al-hikmah, bi al-mauizah al-hasanah, and bi al-muja>dalah al-ahsan. The researcher found that da’wah performed by Sunan Kalijaga was to modificate the figures and the stories of wayang to be filled by Islamic values and phylosophical teaching, as described in the five figures of Pandawa as the representation of five tenets of Islam, they are Yudhistira (Syaha>dah), Bima (Sala>t), Arjuna (Fasting Ramadhan), Nakula (Zaka>h) and Sadewa (Hajj), as well as the figures of Punakawan, which represented people’s life and the way to face its obstacles which has not been exist before in Hindu era. Its represented by Semar, Gareng, Petruk, and Bagong. Thus, the figures of Pandawa and Punakawan influenced the people to finally embraced Islam. ",